Tropical laboratory research to support sustainability issues: A systematic literature review - H. Husamah; Abdulkadir Rahardjanto; Ahmad Adnan Mohd Shukri (Green and Tropical Laboratory for Sustainability, 2024)
Background: The study of tropical laboratory research to support sustainability issues is very urgent to ensure that efforts to conserve and utilize natural resources in tropical areas can be carried out effectively and sustainably. Objectives: This SLR focuses on analyzing research trends in relation to “tropical laboratory research to support sustainability issues”. Methods: This SLR will provide a relatively complete analysis so that it can inspire research activities for researchers, especially in countries that do not yet have a high interest in this aspect. This investigation constitutes a SLR to systematically identify, assess, and analyze all specific research inquiries, topics, or areas. The sequence of inclusion and exclusion was using PRISMA. Data simulation uses "Analyze search results" which is available on the Scopus system. To enrich data and analysis, the data was exported to *CSV format (for visualizing data process with VOSviewer and RStudio) and *RIS (for synchronized with Mendeley). The final result of this process was 17 articles that met the criteria and were worthy of analysis. Results: We discuss the findings related to Tropical Laboratory Research to Support Sustainability Issues based on the established research questions. Conclusion: Publications related to tropical laboratory research for sustainability have shown significant fluctuations since 2004, with the majority of publications coming from the United States. While there is potential for future growth, it is important to increase funding support and collaboration between countries to make this research more effective in supporting sustainability.